DNA transfer when using gloves in burglary simulations. (March 2023) - Carrara, L.; Hicks, T.; Samie, L.; Taroni, F.; Castella, V.
Abstract: Several studies have demonstrated that DNA can be indirectly transferred from an individual onto a surface. Therefore, the presence of DNA that is compatible with a given person does not necessarily mean that this person has touched the surface on which the DNA was recovered. The present work simulates cases, where DNA is recovered on a door handle and compared to several reference DNA profiles. The DNA profile of the trace shares DNA components with a person of interest (POI). When asked about the DNA results, the POI says he has nothing to do with the incident and has never been at the scene. However, a possibility would be that the DNA came from his recently stolen gloves. Someone else, the alternative offender (AO), could have opened the door wearing his gloves (POI's gloves), and transferred his DNA (POI's DNA). Based on the above-mentioned scenario, 60 burglary simulations experiments were carried out to generate data to assess DNA results given these allegations. The quantity and quality of DNA profiles (NGM SElect) recovered when the POI opened/closed the door bare-handed or when someone else performed the same activity but using POI's gloves, were compared. The gloves were regularly worn during at least three months by their owner during the winter. On the contrary, the AO wore them only for two minutes. Among the traces collected on the door handles, less than 50% of the traces led to interpretable DNA profiles. In 30% of the cases (3/10), when the door was opened/closed with bare hands, the DNA found on the door handle led to a mixed DNA profile with the POI's DNA aligning with the major contributor. For the experiments where the AO opened/closed the door with the POI's gloves, the POI's DNA was compatible with 22% (11/50) of the mixed DNA profile, aligning with the major in 8% of the cases (4/50). The DNA profiles of the offices' occupants were observed on the door handles, but not the AO's. In addition to the results of the experiments, we show two examples of how one can assess results observed in casework. Given the possibility of indirect transfer of minute DNA quantities, this research emphasizes the need to evaluate DNA results given the activities when the POI has a legitimate reason that can explain the presence of their DNA. Highlights: DNA transfer when opening doors with and without gloves was investigated. If bare handed, the person of interest's DNA aligned with 30% of the traces. The DNA of the glove owner aligned with 22% of the traces. No DNA from the person who had just "stolen" the gloves was detected. Examples of evaluation given activity level propositions are presented.